Nigericin-induced apoptosis in acute myeloid leukemia via mitochondrial dysfunction and oxidative stress - Arun, Bhavyadharshini; Gopinath, Prarthana; Jha, Anup; Tripathi, Nishtha; Dastager, Syed G.; Hasan, Syed K. (Oncology Research, 2025)
Background: Acute Myeloid Leukemia (AML) is a highly aggressive clonal hematological malignancy with limited treatment options. This study aimed to evaluate the therapeutic potential of nigericin, a polyether ionophore derived from Streptomyces DASNCL-29, as a mitochondrial-targeted agent for AML treatment. Methods: Nigericin was isolated from Streptomyces DASNCL-29 and characterized via chromatography and NMR. Its cytotoxicity was tested in MOLM13 (sensitive and venetoclax-resistant) and HL60 (sensitive and cytarabine-resistant) cells using the MTT assay. Mitochondrial dysfunction was assessed by measuring reactive oxygen species (ROS), mitochondrial membrane potential (Arum), and mitochondrial mass. Apoptosis was evaluated with Annexin V/PI assays and immunoblotting, while proteomic analysis was conducted using Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) to identify differentially regulated proteins. Results: Nigericin demonstrated potent cytotoxicity with IC50 values of 57.02 nM in MOLM13-sensitive, 35.29 nM in MOLM13-resistant, 20.49 nM in HL60-sensitive, and 1.197 nM in HL60-cytarabine-resistant cells. Apoptosis was confirmed by Annexin V/PI staining and caspase-3/PARP cleavage, along with MCL-1 downregulation. Mitochondrial dysfunction was evident from increased ROS, reduced Arum, and decreased mitochondrial mass. Proteomic profiling identified 264 dysregulated proteins, including a 3.8-fold upregulation of Succinate Dehydrogenase [Ubiquinone] Flavoprotein Subunit A (SDHA). Conclusion: Nigericin induces apoptosis in AML cells by disrupting mitochondrial function and enhancing oxidative stress. Its nanomolar potency highlights the need for further mechanistic studies and in vivo evaluations to explore its potential in AML treatment.
Keywords: Acute myeloid leukemia (AML); Antineoplastic agents; Apoptosis; Mitochondrial dysfunction; Nigericin